Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3906/vet-1810-37
|View full text |Cite
|
Sign up to set email alerts
|

On-farm diagnosis of latent respiratory failure in calves

Abstract: The goal of this study was to develop a method for the diagnosis of latent respiratory failure in calves with bovine respiratory disease (BRD) in farm conditions. The study involved 48 calves of the red-motley Holstein breed aged 14-28 days, with no previously experienced BRD, no dyspnea at rest, and a lack of anemia. Group I consisted of 24 calves with spontaneous or induced cough and WI clinical score of ≥5. Group II included 24 calves without spontaneous and induced cough and WI clinical score of ≤3. The de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 20 publications
2
16
0
2
Order By: Relevance
“…Workers who are in contact with toxic gases and dust during Mg production often have abnormally high levels of serum Mg (Beloskurskaya, 2001; Chernitskiy et al, 2019), as confirmed by the present study on workers from workshop 1, where large amounts of Mg dust particles were found floating in the air. The workshop 2 area also contained a small amount of MgO, which was found in the Ti slag dust.…”
Section: Resultssupporting
confidence: 83%
“…Workers who are in contact with toxic gases and dust during Mg production often have abnormally high levels of serum Mg (Beloskurskaya, 2001; Chernitskiy et al, 2019), as confirmed by the present study on workers from workshop 1, where large amounts of Mg dust particles were found floating in the air. The workshop 2 area also contained a small amount of MgO, which was found in the Ti slag dust.…”
Section: Resultssupporting
confidence: 83%
“…They are applied to prevent and treat intestinal infections, to restore the microflora of the digestive tract after antibiotics or antibacterial chemotherapeutic agents. Probiotics improve digestive processes and stimulate non-specific immunity (Andreeva et al, 2018;Khaziakhmetov et al, 2018a;2018b;Chernitskiy et al, 2019). Data on the effectiveness of probiotics in beekeeping are contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…The average peasant farm in the study region should have an area of arable land per farm of about 80 hectares, of the use of horses in other areas [7,8,12,13]. Thus, serious attention is paid to the issues of genetics management, nutrition, technology, veterinary medicine, breeding, and ecology [14][15][16][17][18][19][20][21][22]. In this regard, it is almost impossible to compare productive horse breeding using economic parameters.…”
Section: Resultsmentioning
confidence: 99%
“…This is especially true for droving horse breeding, which is limited in many countries due to limited natural forage lands. A second reason for this is western farmers, especially from economically developed countries, who are most interested in product quality, particularly from a veterinary viewpoint [15,22].…”
Section: Resultsmentioning
confidence: 99%